Características de prescripción de antibacterianos de reserva en pacientes hospitalizados en el servicio de pediatría del hospital Regional Docente de Trujillo período octubre – diciembre 2005 - García Floreano, Marcos Esteban (2006)
Objective: To evaluate the characteristics of use antimicrobial of reservation (AR) in the service of hospitalization of Pediatry of the Hospital Regional Docente de Trujillo. Material and Methods: A descriptive, cross-sectional, prospective study was made that included to the patients hospitalized during the months of October to December of the 2005. This service counts on a total of 36 beds. I consider myself to all the patients hospitalized in this period. The evaluation of the quality of the prescription was made by a physician pediatrist; in addition it was used bibliographical sources. Results: 136 patients and their respective clinical histories included themselves. The prevalence of the prescription of antimicrobial of reservation (PPAR) was 23.31%. The average of prescription of antimicrobial by hospitalized patient was 1.23. The profile of AR consumption demonstrates a monthly increase in the use, with a coefficient of correlation a 0,93 and approximated coefficient of regression of 2.39 DDD/100 bed-day. The specialty of Infectología shows a greater consumption (7.83 DDD) of AR. In relation to the indications for the administration of the medicine, these were made correctly as far as the used dose 94.74%, interval of use 100%, and via of administration 100%. A prescribed 100% of the antimicrobial ones belong to the Petitionary National Essential Medicines (PNEM). Conclusions: The PPAR and average of AR by patient are within the ranks reported in other studies; the AR consumption demonstrates a monthly increase in its use; a greater consumption of AR in the infectología specialty exists; most of used AR it belongs to the PNME, on the other hand the use of AR according to criteria of established use is inside acceptable values